Information Technology and Women's Liberation: Feminism in the Serial Story “Broken Kite” - Elanda, Yelly; Suharnanik, Suharnanik; Asmara, Lusi Rispita (The Journal of Society and Media, 2022)
The woman in the film kite breaking up, which is the subject of this article, is Kinan. Kinan is the main character in the series Layangan Putus which airs on WeTV, telling a love triangle story. Kinan is played by Putri Marino, a woman who can use information technology to reveal the behavior of her cheating husband and then decide to separate. This study uses television program serial media that are trending topics as part of women's position in the household and women's ability to act and speak with their information technology capabilities. The method used in this research is critical discourse analysis or CDA, which is strengthened by a literature study. The results of this study indicate that the film kites break up has accommodated the point of view of women or the female gaze in telling their experiences. Women who are represented in the figure of Kinan are described as active subjects who have choices in determining their behavior and actions. Women use information technology to get out of unhealthy relationships in marriage. Women are better able to show their identity even though they collide with the values that develop in society